2021
DOI: 10.1021/acsnano.1c00030
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Thermoelectric Puddles via the Stacking Order and Electronic Screening in Graphene

Abstract: Thermoelectricity has been investigated mostly on the macroscopic scale despite the fact that its origin is linked to the local electronic band structure of materials. While the role of thermopower from microscopic structures (e.g., surfaces or grain boundaries) increases for emerging thermoelectric materials, manipulating thermoelectric puddles, spatially varying levels of thermoelectric power on the nanometer scale, remains unexplored. Here, we illustrate thermoelectric puddles that can be harnessed via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The concept of puddles has been used in STM and SThEM studies to indicate inhomogeneous charge and thermopower distributions (charge and thermoelectric puddles) 25 . Large-scale thermopower puddles were observed by SThEM on the atomically-flat surface of the commensurate CDW phase in 1T-TaS 2 , as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of puddles has been used in STM and SThEM studies to indicate inhomogeneous charge and thermopower distributions (charge and thermoelectric puddles) 25 . Large-scale thermopower puddles were observed by SThEM on the atomically-flat surface of the commensurate CDW phase in 1T-TaS 2 , as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3b . It has been reported that local band structures produce charge puddles in graphene 25 . In graphene, the weak screening of external impurities produces the spatially-varying charge carrier density (i.e., charge puddles), which can be observed by STM 35 .…”
Section: Resultsmentioning
confidence: 99%
“…[57] Thermopower puddles in exfoliated graphene on an SiO 2 substrate were studied using quantum sensing based on the gatetunable AFM-based SThEM (Figures 4j-l). [73] In SLG, thermoelectric puddles are strongly regulated by the back-gate voltage, whose maximum is located near the CNP (Figure 4k). This can be explained by extremely long-range electron-electron interaction with weak dielectric screening.…”
Section: Afm-based Sthem For Out-of-plane Thermopower At the Atomic S...mentioning
confidence: 99%
“…[ 57 ] Thermopower puddles in exfoliated graphene on an SiO 2 substrate were studied using quantum sensing based on the gate‐tunable AFM‐based SThEM (Figures 4j–l). [ 73 ]…”
Section: Quantum Sensing Of Thermopower From Direct Electrons (Holes)...mentioning
confidence: 99%
See 1 more Smart Citation